Internodule Variation of Anogeissus leiocarpus Gum - Ahmed, Samia Eltayeb; Mohamed, Babiker Elwasila; Karamalla, Karamalla Ahmed (Pakistan Journal of Nutrition, 2009)
Eighteen nodules of Anogeissus Leiocarpus gum were collected randomly from different trees from two different locations (Abojebiha and Elfula) in Sudan. The nodules were analyzed for twelve analytical parameters (moisture%, ash%, nitrogen%, protein%, pH, refractive index, specific rotation, relative viscosity, equivalent weight, uranic acid%, reducing sugars% and tannin %). Analysis of variance showed significant differences (P<0.05) for all parameters studied in each of Abojebiha and Elfula nodules except for the refractive index value which was found to be constant (1.334) in both locations. In addition UV absorption spectra of all nodules gave λ max (247,258,265, 270, 274, 277, 280 and 283).